The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4ra03717k
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic synthesis of triazines from urea: a theoretical study of free radical routes to melamine, ammeline, ammelide and cyanuric acid

Abstract: Prebiotic formation of triazines from urea was studied using density functional theory methods with the aim of understanding some of the neutral precursors that can lead to a mixture of triazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…cyclization) barrier of 15 kcal mol À1 is signicantly smaller than the cNH 2 assisted MM formation from urea (26 kcal mol À1 ). 21 On the other hand, BA formation involves one molecule each of urea and malonic acid, two cNH 2 radicals and release of two cOH and two NH 3 (Scheme 4 and Fig. S3 †).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cyclization) barrier of 15 kcal mol À1 is signicantly smaller than the cNH 2 assisted MM formation from urea (26 kcal mol À1 ). 21 On the other hand, BA formation involves one molecule each of urea and malonic acid, two cNH 2 radicals and release of two cOH and two NH 3 (Scheme 4 and Fig. S3 †).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, B3LYP/6-311G(d,p) calculations have been discussed in this work, in order to allow meaningful comparisons with previous studies. 21,24,29,31 All quantum chemical calculations were carried out using the Gaussian 09 suite of programs. 35…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometry optimizations and zero‐point vibrational energy corrected electronic energies of reactants, transition states, intermediates, and products along the reaction pathways were obtained in the gas phase at B3LYP/6–311G(d,p). This method has been used in analogy with previous studies on radical based pathways of prebiotically important reactions . The stationery points on the reaction pathways were characterized as minima (reactants, intermediates, and products) and saddle points (transition states) using vibrational frequency calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Additionally, a Mg 2+ catalyzed mechanistic pathway for the formation of 2‐pyrimidinone based nucleoside has been explored by Sheng et al However, the high influx of ultraviolet (UV) radiations on primitive earth, coupled with the relevance of radicals to spark discharge experiments, laser‐driven plasma impact simulations, and the presence of cosmic, γ, and UV radiations on the present‐day Titan's atmosphere, suggest that reactions for the formation of nucleobases are likely to follow radical based mechanisms. On these lines, Jeilani et al suggested a free radical route for the formation of triazines and pyrimidines from urea in a water‐ice mixture, and further formulated free radical based mechanisms for the formation of these pyrimidines from 1,2‐diaminomaleonitrile and formamide, acetylene and urea, as well as formamide and HCN or acetylene . Similarly, Ferus et al theoretically explored a radical induced, formamide based synthesis of nucleobases in a high energy impact scenario …”
Section: Introductionmentioning
confidence: 99%